2013
DOI: 10.1002/cnm.2583
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis on longitudinal and radial functionally graded femoral prosthesis

Abstract: This study focused on developing a 3D finite element model of functionally graded femoral prostheses to decrease stress shielding and to improve total hip replacement performance. The mechanical properties of the modeled functionally graded femoral prostheses were adjusted in the sagittal and transverse planes by changing the volume fraction gradient exponent. Prostheses with material changes in the sagittal and transverse planes were considered longitudinal and radial prostheses, respectively. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Therefore, the highest level of stress shielding is depicted due to the highest stiffness of this stem. Conversely, HGP and FGP stems yielded higher stress transfer to the bone in all the Gruen zones, and hence offered less stress shielding . Another important observation is that the stress values are almost identical in the distal end of the femur (Gruen zone 4) for all the tested stems (around 30 MPa).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, the highest level of stress shielding is depicted due to the highest stiffness of this stem. Conversely, HGP and FGP stems yielded higher stress transfer to the bone in all the Gruen zones, and hence offered less stress shielding . Another important observation is that the stress values are almost identical in the distal end of the femur (Gruen zone 4) for all the tested stems (around 30 MPa).…”
Section: Resultsmentioning
confidence: 88%
“…The advantage of FGM is to tailor and control the mechanical properties of the stem to match the surrounding bone . Oshkour et al have conducted a finite‐element analysis on functionally graded femoral stems in the longitudinal and radial directions. The results have shown that increasing the grading exponent has led to an increase in the strain energy experienced by the bone, hence less stress‐shielding effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[95] [104,105] for the femoral component of a knee through functionally graded composition. Three different material combinations were suggested: titanium, cobalt chromium, and hydroxyapatite.…”
Section: Porositymentioning
confidence: 99%
“…It is important to emphasize that the knee contact force behaviors are activity-specific and the optimal design of the TKR may lead to maximizing the clinical outcomes. However, the implant design may be optimized when its effect on the musculoskeletal tissues and structures could be elucidated [5]. Joint contact forces play an important role in the understanding of the effect of the implant on the joint behavior and musculoskeletal load [6].…”
Section: Introductionmentioning
confidence: 99%